Features of Emotional and Social Development in Preschool Children with Sensorineural Hearing Loss (Texas Journal of Medical Science, 2026)
Sensorineural hearing loss significantly affects speech acquisition, cognitive development, and social adaptation in children. Investigation of the psycho-emotional profile of preschool children with sensorineural hearing loss is essential for developing effective interventions.